Virtual reality for acute pain in outpatient hysteroscopy: a randomised controlled trial. (22nd July 2020) - Deo, N; Khan, KS; Mak, J; Allotey, J; Gonzalez Carreras, FJ; Fusari, G; Benn, J
Abstract : Objective: To evaluate the effectiveness of virtual reality as a distraction technique in the management of acute pain and anxiety during outpatient hysteroscopy. Design: Parallel group, prospective randomised controlled trial. Setting: UK University Hospital. Methods: Forty consenting, eligible women were randomised to virtual reality intervention (immersive video content as a distraction method) or standard care during outpatient hysteroscopy from August to October 2018. Main outcome measures: Pain and anxiety outcomes were measured as a numeric rating score (scale 0–10). Results: Compared with standard care, women with virtual reality intervention experienced less average pain (score 6.0 versus 3.7, mean difference 2.3, 95% CI 0.61–3.99, P = 0.009) and anxiety (score 5.45 versus 3.3, mean difference 2.15, 95% CI 0.38–3.92, P = 0.02). Conclusion: Virtual reality was effective in reducing pain and anxiety during outpatient hysteroscopy in a mixed‐methods randomised control trial. Its wide potential role in ambulatory gynaecological procedures needs further evaluation. Tweetable abstract: Virtual reality can be used as a part of a multimodal strategy to reduce acute pain and anxiety in patients undergoing outpatient hysteroscopy. Tweetable abstract: Virtual reality can be used as a part of a multimodal strategy to reduce acute pain and anxiety in patients undergoing outpatient hysteroscopy.